Clinical and Imaging Features of a Focal Intrahepatic Biliary Stricture Visualized Only as Duct Dilatation - Byoung Je Kim; Min Seong Kim; Mi Jeong Kim; Jae Hyuck Yi; Jin Hyuk Paek; Hye Won Lee; Chan Hee Park; Gisu Lee; Koo Jeong Kang (Journal of the Korean Society of Radiology)
Purpose We assessed the proportion of patients with a focal intrahepatic stricture (FIHS) that was a precursor lesion or malignancy and visualized only as a duct dilatation. Materials and Methods This retrospective study assessed patients who underwent surgery or biopsy for an FIHS on CT or MRI between January 2010 and March 2022. The number and proportion of non-precursor benign lesions, precursors, and malignancies were calculated. Clinical variables and imaging features were compared between non-premalignant benign and premalignant/malignant FIHSs. Results Twenty-eight patients with confirmed histopathological diagnoses were identified, including 15 men (54.0%) and 13 women (46.0%). The median age of all patients at the first imaging diagnosis was 65 ± 9.54 (range, 43–78) years. Of the 28 patients with FIHSs, 9 (32%) were diagnosed with cholangiocarcinoma and 7 (25%) were diagnosed with precursor lesions, which included six intraductal papillary neoplasms of the bile duct and one biliary intraepithelial neoplasm. Accordingly, 16 (57%) patients had malignant or precursor lesions, and 12 (43%) were diagnosed with non-precursor benign lesions. None of the clinical variables and imaging features used for analysis showed a statistically significant difference between the non-premalignant benign and premalignant/malignant FIHS groups (p > 0.05). Conclusion FIHSs visualized only as duct dilatation can harbor malignant or precursor lesions.